Majas Gaya Bahasa pada Lirik Lagu “Asmalibrasi”: Analisis Gaya Bahasa dan Stilistika - Resti Rahmatilah (Universitas Katolik Widya Karya Malang, 2023)
The purpose of making this journal is to find out the meaning of the lyrics of the song